Pelatihan Diversifikasi Produk Olahan Jagung Manis pada Tutor Pendidikan Anak Usia Dini di Kecamatan Makasar, Jakarta Timur - . Alsuhendra; . Ridawati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Knowledge and skills about food to be consumed by an early child is one of the important things that need to be mastered by the tutor of Early Childhood Education (ECE). This activity was aimed to improve the knowledge and skills in diversity processing sweet corn products ECE tutors in subdistrict Makasar, East Jakarta. This activity was conducted in PAUD Kuntum Melati, Makasar Village, East Jakarta on September 29, 2015. The method used is counseling and demonstration with pre-activity stage, implementation, evaluation of target knowledge, and motivation. The results showed that the activity could improved the knowledge and skills of ECE tutors about sweet corn, the nutritional content, and its products, sweet corn beverage and kue talam from corn waste. All tutors liked the taste, color, and aroma of corn extract beverage and talam cake.